An Innovative Strategy Based on Secure Element for Cyber–Physical Authentication in Safety-Critical Manufacturing Supply Chain - Ernesto Gómez-Marín; Valerio Senni; Luis Parrilla; Jose L. Tejero López; Encarnación Castillo; Davide Martintoni (Applied Sciences, 2023)
The accurate tracking of every production step and related outcome in a supply chain is a stringent requirement in safety-critical sectors such as civil aviation. In such a framework, trusted traceability and accountability can be reliably and securely managed by means of blockchain-based solutions. Unfortunately, blockchain cannot guarantee the provenance and accuracy of the stored information. To overcome such a limitation, this paper proposes a secure solution to strongly rely on the tracking information of the physical assets in the supply chain. The proposed solution exploits Hardware Security Modules (HSMs) to provide required cryptographic primitives through a Near-Field Communication (NFC) connection. In our approach, each transfer of the assets is authenticated, verified, and recorded in the blockchain through the HSM. Transaction entries are signed, thus providing a guarantee of ownership and authenticity. The proposed infrastructure has been subject of an exhaustive security analysis and proved resilient against counterfeiting attempts, stakeholder repudiations, and misleading information.